Penyuluhan Tentang Pentingnya Penggunaan Keluarga Berencana (KB) Pada Pasangan Usia Subur (PUS) di WilayahKerja Puskesmas Darfuar Kecamatan Biak Kota - Heni Voni Rerey; Sri Wahyuni (Rena Cipta Mandiri, 2026)
Limited knowledge among fertile couples regarding contraceptive methods, the continued dominance of three-month injectable contraceptives, and low male involvement in family planning remain important reproductive health challenges. Data from the Darfuar Community Health Center, Biak City District, identified 350 fertile couples as the target population for family planning services, with injectable contraception being the most commonly used method. This community service program aimed to improve participants’ knowledge of family planning, contraceptive options, and the importance of husbands’ participation in reproductive decision-making. Health education was delivered through interactive lectures, discussions, question-and-answer sessions, and educational leaflets involving 35 fertile couples. Evaluation using pre-test and post-test assessments demonstrated an increase in the average knowledge score from 64.3 to 88.6, representing a 24.3-point improvement. Participants also showed better understanding of family planning benefits, long-acting reversible contraceptive methods (LARCs/MKJP), and husbands’ supportive roles. These findings indicate that health education effectively improves family planning knowledge and should be implemented continuously by involving health workers, community health volunteers, community leaders, and married couples to promote informed contraceptive choices and strengthen male participation in family planning.